Effects of chitosan-assisted moderate-intensity exercise on metabolic parameters and lower-limb biomechanical characteristics in overweight adults: a randomized controlled trial - Zhang, Jianwei; Liu, Haiyan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundOverweight is a major risk factor for metabolic disorders and joint injuries. Exercise and dieting alone often fail to yield ideal outcomes due to issues like non-compliance and safety concerns. Polysaccharides, such as chitosan, are promising in regulating lipids, glucose, and aiding weight loss. However, the combined effects of chitosan supplementation and exercise on lower limb biomechanics and metabolic health remain underexplored.ObjectiveTo assess the effects of chitosan supplementation combined with moderate-intensity exercise on metabolic parameters and lower limb biomechanics in overweight adults, and to evaluate the intervention’s safety, compliance, and feasibility for clinical and community-based management.MethodsA single-center, parallel-group, randomized controlled trial (RCT) was conducted with 60 overweight adults. Participants were randomly assigned to one of three groups: polysaccharide plus exercise, exercise-only, or control group, with a 12-week intervention period. The polysaccharide plus exercise group received 3,000 mg of daily chitosan alongside moderate-intensity exercise, while the exercise-only group participated in the same exercise routine without supplementation. The control group maintained their usual lifestyle. Primary outcomes included changes in body composition, metabolic indices, and lower limb biomechanics. Compliance and adverse events were recorded. Data were analyzed using one-way ANOVA, repeated-measures ANOVA, and Bonferroni correction (P < 0.05).ResultsNo significant baseline differences were found across groups (P > 0.05). After 12 weeks, the polysaccharide plus exercise group showed significantly greater reductions in body weight and waist circumference compared to the exercise-only and control groups (P < 0.05). BMI, hip circumference, and total body fat mass were also significantly lower than the control group (P < 0.05). The polysaccharide plus exercise group exhibited superior improvements in HOMA-IR, total cholesterol, triglycerides, LDL, and HDL (P < 0.05), and showed more substantial reductions in maximum plantar pressure and peak ground reaction force (P < 0.05). Compliance in this group was significantly higher than in the exercise-only group (P = 0.002). No significant differences in adverse events were observed (P > 0.05).ConclusionChitosan supplementation combined with moderate-intensity exercise significantly improved body weight, metabolic parameters, and lower limb biomechanics in overweight individuals, with good compliance and safety. This intervention offers a promising strategy for managing overweight and related metabolic issues.